A succinonitrile-infiltrated silica aerogel synergistically-reinforced hybrid solid electrolyte for durable solid-state lithium metal batteries. (20th January 2022) - Liu, Ling; Cai, Yinghui; Zhao, Zhikun; Ma, Chengwei; Li, Chunli; Mu, Daobin
Abstract : New fast Li + ion transport pathways were available in the developed SSP material, enabling high ionic conductivity. Abstract : Hybrid solid electrolytes have been widely studied due to their favorable flexibility, high mechanical strength, and good interfacial contact with electrodes. However, the relatively low ionic conductivity of hybrid solid electrolytes and poor interfacial compatibility restrict their practical application. In this study, a succinonitrile electrolyte (SNE) infiltrated silica aerogel (SAG)/polyacrylonitrile (PAN) hybrid solid electrolyte (SSP) was fabricated. As-prepared SSP exhibits high ionic conductivity of 7.45 × 10 −4 S cm −1 (30 °C) and a high t Li + transference number of 0.70. This is attributed to the synergistic effect of the porous skeleton of SAG and the high conductivity of SNE providing multiple Li + transport channels. In-depth analysis demonstrates that SSP possesses fast Li + mobility and plenty of freely mobile Li + ions and it exhibits favorable interfacial compatibility with the anode and cathode. As a result, a symmetrical Li/SSP/Li cell can undergo long-term cycling for 700 h at 0.1 mA cm −2 . Moreover, an NCM811/SSP/Li cell could exhibit a high discharge capacity of 200.5 mA h g −1 at 0.1 C and excellent rate performance with a capacity of 80.8 mA h g −1 at 5 C. Remarkably, the NCM811/SSP/Li cell demonstrates outstanding cycling stability with 73.2% capacity retention after 200 cycles at 1 C.